Supramolecular Materials: Multifunctional Supramolecular Hybrid Materials Constructed from Hierarchical Self‐Ordering of In Situ Generated Metal‐Organic Framework (MOF) Nanoparticles (Adv. Mater. 30/2015). (August 2015) - Chaudhari, Abhijeet K.; Han, Intaek; Tan, Jin‐Chong
<x xml:space="preserve">Abstract</x> The supramolecular engineering of a new family of hybrid gels coexisting with metal–organic framework (MOF) nano‐particles created in situ is demonstrated by J. C. Tan and co‐workers on page 4438. The rapid process of inorganic–organic self‐assembly generates a hierarchical fiber network architecture, whose electrical conductivity and mechanical characteristics can be tuned to yield a range of bespoke soft matter with unconventional properties.